2021
DOI: 10.1038/s41598-021-03225-8
|View full text |Cite
|
Sign up to set email alerts
|

The long term participation trend for the colorectal cancer screening after the 2011 triple disaster in Minamisoma City, Fukushima, Japan

Abstract: Colorectal cancer (CRC) screening is a well-established cancer screening method, and its effectiveness depends on maintaining a high participation rate in the target population. In this study, we analyzed the trends in CRC screening participation rates over 10 years in Minamisoma City, where residents were forced to evacuate after the 2011 triple disaster in Fukushima, Japan. The immunochemical fecal occult blood test is provided as municipal CRC screening. We calculated the annual CRC screening participation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…We previously reported comparable outcomes for local colorectal cancer screening using fecal occult blood in Minamisoma City 13 . However, there are two important differences between breast and colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We previously reported comparable outcomes for local colorectal cancer screening using fecal occult blood in Minamisoma City 13 . However, there are two important differences between breast and colorectal cancer screening.…”
Section: Discussionmentioning
confidence: 90%
“…There has been a growing concern over the past few years about the effects of disasters and crises on breast cancer screening, an argument that has been further enhanced by the novel coronavirus disease 2019 (COVID-19) pandemic 10 , 11 . Before this pandemic, only a few studies had evaluated the effect of disasters and crises on cancer screening programs as a whole 12 , 13 . However, since the beginning of the global coronavirus disease (COVID-19) pandemic in November 2019, a global decline in screening rates for breast cancer and other cancers has been reported 14 – 18 .…”
Section: Introductionmentioning
confidence: 99%
“…What is noteworthy is that long-term health damage regarding cancer was observed after the triple disaster. In our previous studies, help-seeking was found to decline over 5 years (3) , and screening coverage declined over 3 years before returning to the predisaster level (4) , Despite the limited impact on infrastructure after the triple disaster, the impact on cancer care is likely to be more prolonged this time.…”
mentioning
confidence: 83%
“…4 Department of Radiation Health Management, Fukushima Medical University School of Medicine, Fukushima, Japan. 5 Department of Internal Medicine, Serireikai Group Hirata Central Hospital, Ishikawa District, Fukushima, Japan. 6 Department of Psychiatry, Hori Mental Clinic, Minamisoma, Fukushima, Japan.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Disasters cause a wide range of short-and long-term health problems. Short-term impacts include problems related to supplies and lifelines [1,2], medium-term impacts include problems related to physical and mental functional decline while living in shelters [3,4], and longterm impacts include problems related to the rebuilding of communities in the affected areas [5][6][7][8][9][10]. Although risk management efforts, risk reduction frameworks, and relevant policies continue to address disasters and strengthen disaster management efforts, minimizing the impact of disasters remains challenging [11].…”
Section: Introductionmentioning
confidence: 99%